MENINGKATKAN KETERAMPILAN PROSEDURAL SISWA KELAS VIII E SMP NEGERI 31 BANJARMASIN MELALUI MODEL PENGAJARAN LANGSUNG PADA PEMBELAJARAN IPA FISIKA - Dandan Wicaksono; Muhammad Arifuddin; Misbah Misbah (Jurnal Ilmiah Pendidikan Fisika, 2017)
Learning outcome and procedural skills students are still classified as low, as in school learning model did not match expectation. So, it will be done research on improving learning outcomes and procedural skills of the students through direct instruction of physics IPA learning. This research aims to describe (1) The fidelity of lesson plans during the process of teaching and learning through direct instruction, (2) Procedural skills of students through direct instruction, (3) Learning outcome through direct instruction. This research is a research action class that consists of two cycles with model Hopkins. The subject of research is the grade VIII E The middle state 31 Banjarmasin. The data collection using to the test, and observations. Analytical techniques descriptive quantitative and qualitative data. The results showed that (1) The fidelity of lesson plans during the process of teaching and learning through direct instruction increase in cycle I gained average score of 86,04% became 97,26% cycle II, (2) and procedural skills students also experienced an increase in cycle I gained an average score of 82,76% became 94,83% in cycle II, (3) Learning outcome experience increased where thoroughly the results of the study on cycle I of 48,28% became 89,66%. Provide the conclusion that with the use of the few phase direct instruction in the process of learning can improve the procedural skill and the student learning as expected.